Divergent thinking in groups during cold-water immersion is impaired by cold stress not the cold shock response - Max Kailler Smith; Max Kailler Smith; Rebecca Weller; Rebecca Weller; Tony Duong; Tony Duong; Rebecca McClintock; Rebecca McClintock; Matthew Peterson; Nathaniel Barr; Douglas M. Jones; Timothy L. Dunn (Frontiers in Psychology)
IntroductionA primary hazard of working in cold maritime environments is the potential for a substantial man overboard situation in freezing waters. Sudden cold-water immersion (CWI) triggers the cold shock response (CSR), which consists of cardiorespiratory responses that increase the chance of drowning. If cold shock response severity can be mitigated, life-saving actions must be taken within the first 10 min, as after this time frame drowning occurs due to cold incapacitation. To date, research shows that executive functioning is generally impaired by intense, acute stress, which implies the ability to think through potential actions to maximize survival would also be impaired by the cold shock response.MethodsTo examine whether the severity of cold shock response impairs higher-level thinking in a group, 29 active duty service members completed a group format Divergent Association Task (DAT; 4–5 per group) prior to and during a 13-min cold-water immersion (water temperature: 1.3°C, air temperature: −2.7°C).ResultsResults showed no relationship between cold shock response magnitude, indexed by peak heart rate, and DAT performance. However, results indicated that those with lower skin temperatures performed worse on the DAT.DiscussionResults suggest that the ability to engage in divergent thinking is relatively preserved in the critical ~10-min window although skin cooling may bias attention toward the cold stress impacting task performance. Furthermore, subjective reports of the severity of the initial gasp tracked with peak heart rate demonstrating potential utility of subjective responses in the absence of respiratory measurements.